Low-cost piezoelectric sensors and gamma ray attenuation fabricated from novel polymeric nanocomposites - Shaimaa Mazhar Mahdi; Majeed Ali Habeeb (AIMS Materials Science, 2023)
This study looks at the synthesis of innovative PEO/PVA/SrTiO3/NiO nanocomposites for piezoelectric sensors and gamma shielding applications that are low weight, elastic, affordable and have good gamma ray attenuation coefficients. The impact of SrTiO3/NiO on the structural characteristics of the PEO/PVA mixture is investigated. The polymer mixture PEO/PVA received additions of SrTiO3/NiO at concentrations of (0, 1, 2, 3 and 4) weight percent by the casting method. On the top surface of the films PEO/PVA/SrTiO3/NiO NCs, scanning electron microscopy reveals several randomly distributed aggregates or fragments that are consistent and coherent. An optical microscope image collection reveals that the blend*s additive distribution of NPs was homogenous. Gamma ray shielding application results show that the attenuation coefficient of PVA/PEO/SrTiO3/NiO NCs is increased by increasing concentration of SrTiO3/NiO nanoparticles. Radiation protection is another application for it. The pressure sensor application findings of NCs show that, when the applied pressure rises, electrical capacitance (Cp) increase.